Experimental Modelling And Control Of Linear Actuator For Manufacturing Applications - Pozai, Nurul Natasha Aiza (Universiti Sains Malaysia, 2022)
This study describes an automated Kuih Loyang’s simulation machine that was developed to replace the manual process and thereby boost Kuih Loyang production. The pneumatic cylinder and Arduino UNO were utilised by the machine to accomplish the automatic system. The machine is programmed to do the dipping stage, which includes shaking parts of the mould frame to remove all of the Kuih Loyang from the mould. It was discovered to be capable of properly completing the tasks coded in the Arduino IDE. This research compares the vibration value of the simulation machine to the manual machine in the factory by measuring the vibration produced by the shaking of the mould frame. As a result, a system capable of measuring the acceleration of the mould frame during shaking has been created to measure the vibration in terms of acceleration. The MPU6050 was used to measure the acceleration in terms of the metre per second squared. The device takes raw data from an accelerometer mounted on the mould frame and processes it using an Arduino UNO controller to compute gravitational values. The gravitational values then minus with the offset values to obtain the actual data for the acceleration in g unit. Next, the machine shaking is analysed by determining the frequency and amplitude of the mould frame. Data from the Arduino is serially delivered to the monitoring system, where it is saved in an excel file. Then, in Excel, the Fast Fourier Transform (FFT) is used to convert the time domain G-values to the frequency domain. After executing the Fast Fourier Transform (FFT), the frequency and amplitude are obtained. Excel was used to create a graph of acceleration versus time and frequency versus amplitude. According to the statistics, the simulation machine shakes three times, resulting in maximum accelerations of 1.01g, 0.79g, and 0.57g, while the manual machine at the factory shakes only once. The manual machine's maximum acceleration at the factory is 1.03g. The simulation machine's highest frequency is 79 Hz followed by 10 Hz, while the manual machine's highest frequency is 12 Hz followed by 53 Hz. This demonstrates that the simulation machine, like the manual machine, was able to remove all of the Kuih Loyang from the mould during the dipping stage. This study successfully demonstrates this.